Foreword (OverHolland, 2017)
We have great pleasure in presenting a new issue of OverHolland. It has taken a while, but following SUN Architecture’s decision not to publish any more issues in the series, the Vantilt publishing company has now taken over where SUN left off. In the meantime, the copy has been piling up, which is why this is another double issue.OverHolland 12/13 opens with an article by the Spanish architect Gabriel Carrascal Aguirre on ‘The space of cartography’ – the subject of his dissertation for the Villard d’Honnecourt International Doctorate in Architecture Ph. D. programme in Venice in 2011. He defends the view that cartography should never be treated as a neutral research instrument, for every map is a well-defined reading of reality and as such can form a link between research and design.This view is well illustrated in Like Bijlsma and Eireen Schreurs’s article ‘Harvesting’. Even though the recent economic crisis has put an end to the large-scale development of city districts, the two architects’ design for the Dutch city of Haarlem shows that there are still plenty of ways to revitalise cities. A close reading of urban expansion on the eastern side of Haarlem has revealed numerous starting points for a different approach based on hitherto unexploited assets in the area. This approach is broadly outlined in the explanatory section.Not that it is altogether new. In earlier articles for OverHolland, Esther Gramsbergen has shown that various places in Amsterdam were repeatedly the scene of architectural interventions in the successive periods of its urban development. Under constantly changing conditions, the Dam square, the monastery and convent district and the Plantage were triggers for the development of new urban institutions such as the Stock Exchange, the Binnengasthuis hospital and the Illustrious School (the forerunner of today’s University of Amsterdam). In her article for this issue of OverHolland, ‘Putting science on the map’, Gramsbergen explains the transformation of the Plantage in the course of the nineteenth century, focusing in particular on King Louis Bonaparte’s ambitions for the area and the later development of the Artis zoo. This was the closing chapter of her dissertation for the Villard d’Honnecourt programme in Venice in 2011, entitled Inner fringe belts and the formation of the knowledge infrastructure in Amsterdam, 1578-1880.Cartography is also an ideal way to gain insights on a higher scale into the interplay of landscape and urbanisation. Following on from Freek Schmidt’s ‘Dutch Arcadia: Amsterdam and villa culture’ in OverHolland 10/11, Gerdy Ver-schuure lays the foundations for a broader land-scape-typology analysis of country estates in North and South Holland. Her article ‘A pleasing view’ focuses on the role of landscape features in the composition of the design for various country estates.Reinout Rutte and Henk Engel then explore, from the point of view of historical geography, two areas that are now peripheral to the Randstad. Rutte’s ‘Four hundred years of urban development in the Scheldt estuary’ sets out to identify the changes in navigation routes and trade flows that affected the distribution pattern and development of towns in the south-western delta. As for Henk Engel, he takes a closer look at the area of Holland north of the River IJ. His ‘Distribution of towns, cities and infrastructure in Holland’s Northern Quarter up to around 1700’ examines how existing literature on the area has attempted to grasp the relationship between geographical environment, socioeconomic developments and political events.Finally, some of the themes in this issue of OverHolland form the basis for the book reviews in the ‘Polemen’ section. Jaap Evert Abrahamse and Jan van Doesburg discuss Jerzy Gawronski’s Amsterdam Ceramics and P. J. Knegtmans’s Amsterdam: een geschiedenis (‘Amsterdam: a history’), with critical commentary on both publications. And Herman van Bergeijk wonders whether Balans tussen stad en platteland (‘Striking a balance between town and country’), a four-volume study of the de-urbanisation of Zeeland between 1750 and 1850 by Paul Brusse, Jeanine Dekker, Arno Neele and Wijnand Mijnhardt, really does provide a new template for Dutch history.